Novel circular RNA circ_0086722 drives tumor progression by regulating the miR-339-5p/STAT5A axis in prostate cancer. (1st May 2022) - Deng, Wen; Zhou, Xiaochen; Zhu, Ke; Chen, Ru; Liu, Xiaoqiang; Chen, Luyao; Jiang, Hao; Hu, Bing; Zeng, Zhenhao; Cheng, Xiaofeng; Yao, Zhijun; Nie, Jianqiang; et al.
Abstract: Recent studies validate that circular RNAs have played critical regulatory functions in cancer biology. However, their contribution to prostate cancer (PCa) remained largely unclear. Our study aimed to explore the regulatory function and underlying mechanisms of circ_0086722 in PCa. The circ_0086722 levels in PCa tissues and cell lines were detected through qRT-PCR. In vivo and in vitro experiments were performed to evaluate the functions of circ_0086722 in PCa. Subsequently, the underlying mechanisms of circ_0086722 were explored with qRT-PCR, RNA immunoprecipitation, miRNA pull-down, and luciferase reporter assay experiments. Results revealed that circ_0086722 was highly expressed in PCa tissues and cell lines. Furthermore, high levels of circ_0086722 were positively correlated with pT3 stage, higher specimen Gleason score (>7), and worse biochemical recurrence-free survivals of PCa patients. Then, functional experiments revealed that circ_0086722 accelerated PCa proliferation and progression. Moreover, we demonstrated that circ_0086722 could mechanistically relieve the repressive effects of miR-339-5p on its target STAT5A, which facilitates PCa development. In conclusion, our findings revealed that circ_0086722 drives PCa development via the miR-339-5p/STAT5A axis, and it may function as a potential prognostic biomarker or therapeutic target for PCa treatment. Further studies with large sample sizes and sufficiently long follow-up periods are necessary to confirm the predictive role of circ_0086722 for the prognosis of PCa patients. Highlights: Circ_0086722 could be a potential prognostic biomarker or therapeutic target for prostate cancer treatment. High circ_0086722 level was positively correlated with pT3 stage and higher specimen Gleason score of prostate tumors. Circ_0086722 was preferentially localized in the cytoplasm of prostate cancer cells. Circ_0086722 accelerate the proliferation and progression of prostate cancer in vitro and in vivo. Circ_0086722 drives prostate cancer development via the miR-339-5p/STAT5A axis.